Аналитическое исследование существующих систем пополнения боекомплекта РСЗО БМ-21 "ГРАД" и сравнение их с транспортно-заряжающей машиной разработки ГП "ХКБМ" - Гращенков, Г. П.; Кроленко, А. И.; Сливар, Е. Я.; Касьян, Р. В.; Андрус, С. Г. (НТУ "ХПИ", 2018)
У статті розглянуті шляхи оптимізації процесу заряджання реактивних систем залпового вогню на основі дослідження наявних механізмів, вирішуючих дане завдання на існуючих реактивних системах світових виробників, а також результатів практичної перевірки оригінальних конструкторських рішень, способу й методики розроблених ГП "ХКБМ".

The article considers ways to optimize the uploading process of rocket launcher systems based on research of available mechanisms,that solve this problem on existing rocket systems of world manufacturers, as well as the results of practical testing of original design solutions, the method and methodology developed by the State Enterprise "KMDB".
Analytical investigation of existing systems of MLRS BM-21 "GRAD" ammunition upload and their comparison with the transporter loader designed by se "KMDB"
Keywords: реактивные системы залпового огня; пусковая установка; боевой расчет; стыковочные замки; задние аутригеры